Assessment of the Risk of Failure in Electric Power Supply Systems for Railway Traffic Control Devices - Tomasz Ciszewski; Jerzy Wojciechowski; Mieczysław Kornaszewski; Grzegorz Krawczyk; Beata Kuźmińska-Sołśnia; Artur Hermanowicz (Sensors)
This paper provides a reliability analysis of selected components in the electrical power supply systems used for railway traffic control equipment. It includes rectifiers, controllers, inverters, generators, batteries, sensors, and switching elements. The study used failure data from power supply system elements on selected railway lines. The analysis was performed using a mathematical model based on Markov processes. Based on the findings, recommendations were made to improve safety levels. The results presented in the paper could serve as a valuable source of information for operators of power supply systems in railway traffic control, helping them optimize maintenance processes and increase equipment reliability.